9 Step-by-step explanation: 6.4 × 3 =19.2 44.4 – 19.2 =2.8y 25.2=2.8y 25.2/2.8=y y=9

Simplify: (6.4)(3)+2.8y=44.4 19.2+2.8y=44.4 2.8y+19.2=44.4 Subtract 19.2 from both sides. 2.8y+19.2−19.2=44.4−19.2 2.8y=25.2 Divide both sides by 2.8. 2.8y/2.8 = 25.2/2.8 y=9

check to make sure we are correct:6.4(3) + 2.8(9) = 44.4

9 Step-by-step explanation: plug 3 into the x, then use the order of operations/ pemdas to solve. first multiply 6.4 and 3 (=19.2) then subtract the answer from 44.4 (now the equation is 2.8y=25.2) then divide 2.8 from 25.2 to get x alone and you are left with x=9

19.2 + 2.8y = 44.4-19.2 -19.2 2.8y = 25.2/ 2.8 / 2.8 y = 9

Answer y=45 Step-by-step explanation:

9 Step-by-step explanation: plug 3 into the x, then use the order of operations/ pemdas to solve. first multiply 6.4 and 3 (=19.2) then subtract the answer from 44.4 (now the equation is 2.8y=25.2) then divide 2.8 from 25.2 to get x alone and you are left with x=9

- How do you pronounce Akhal Teke? - January 25, 2023
- 21 june, gemini or cancer?!? - January 25, 2023
- What idea is the narrator in ‘exhalation’ most clearly promoting to the reader? - January 25, 2023